Robust and Automatic Waste Segregator - Balpande, A.V; Sathawane, H.S; More, S.S; Bisht, S.S (International Journal of Computer Sciences and Engineering, 2020)
In past years, the human population living in urban areas has been increasing. This has created large quantities of waste. Since civic authorities tend to overlook this major concern, the untreated waste causes pollution in our environment and creates unhygienic conditions for the citizens. If this waste is treated properly then it becomes useful for us. Proper handling of this situation by our method, can lead to cleaner surroundings for the citizens, efficient treatment of the waste and it can also be financially profitable for the authorities. Our method proposes segregation of waste into various categories based on its property. We accomplish this by using a system made of multiple sensors embedded with a micro-controller which can classify various types of materials. The system segregates waste into dry, wet, metallic and non metallic categories. This leads to better processing of each category separately, which is a more efficient method. The segregated waste can be reused, recycled or used in landfills depending on its category. Also our system monitors the fill level of waste in the dustbins so that it can be collected on time by the concerned authorities. This method leads to better utilisation of waste.